Control of cobalt catalyst thin film thickness by varying spin speed in spin coating towards carbon nanotube growth - Zulkapli, Nor Najihah; Abd Manaf, Mohd Edeerozey; Ab Maulod, Hairul Effendy; Abdul Manaf, Nor Syafira; Raja Seman, Raja Noor Amalina; Bistamam, Mohd Shahril Amin; Talib, Elyas; Mohd Abid, Mohd Asyadi Azam (Trans Tech Publications, 2015)
Cobalt (Co) catalyst thin film is an active metal catalyst that can be very helpful to grow carbon nanotubes (CNTs). The catalyst thin films were prepared on silicon wafers by spin coating the solution of cobalt acetate tetrahydrate and ethanol. The effects of different spin speed parameter during the spin coating process were investigated. The findings showed that the optimum thickness of the Co catalyst thin films, i.e., 12.1 nm, was obtained at the highest spin speed of 8000 rpm. The uniformity of the thin films was also found to increase with increasing spin speed. The study also demonstrated that single-walled carbon nanotubes could be grown from Co catalyst particles after the catalytic chemical vapor deposition of ethanol. The particle and thickness analysis, as performed by means of FESEM while the existence of CNTs, was performed by Raman spectroscopy.